Tunable Modal Birefringence in a Low‐Loss Van Der Waals Waveguide. Issue 27 (10th May 2019) - Hu, Debo; Chen, Ke; Chen, Xinzhong; Guo, Xiangdong; Liu, Mengkun; Dai, Qing
Abstract: van der Waals (vdW) crystals are promising candidates for integrated phase retardation applications due to their large optical birefringence. Among the two major types of vdW materials, the hyperbolic vdW crystals are inherently inadequate for optical retardation applications since the supported polaritonic modes are exclusively transverse‐magnetic (TM) polarized and relatively lossy. Elliptic vdW crystals, on the other hand, represent a superior choice. For example, molybdenum disulfide (MoS2 ) is a natural uniaxial vdW crystal with extreme elliptic anisotropy in the frequency range of optical communication. Both transverse‐electric (TE) polarized ordinary and TM polarized extraordinary waveguide modes can be supported in MoS2 microcrystals with suitable thicknesses. In this work, low‐loss transmission of these guided modes is demonstrated with nano‐optical imaging at the near‐infrared (NIR) wavelength (1530 nm). More importantly, by combining theoretical calculations and NIR nanoimaging, the modal birefringence between the orthogonally polarized TE and TM modes is shown to be tunable in both sign and magnitude via varying the thickness of the MoS2 microcrystal. This tunability represents a unique new opportunity to control the polarization behavior of photons with vdW materials. Abstract : In a well‐designed van der Waals (vdW) waveguide, the orthogonally polarized ordinary and extraordinary guided modes can be degenerate and propagate with the same phase velocity. This means that the photons propagate through the anisotropic waveguide without altering their polarization state, just like they propagate through an isotropic bulk material. In this sense, the observed phenomenon can be summarized as "isotropy from anisotropy."